Michelia alba: A Review on Its Biological Profile and Ethnobotany in Java - Ahmad Naharuddin Ramadhan; MK Antony; SP Pradana; Susi Dewiyeti (Jurnal Indonesia Sosial Teknologi, 2025)
Michelia alba DC (white champaca) is an ornamental, flowering, and aromatic plant that grows widely in tropical and subtropical areas of Southeast Asia. This plant has long been known as a medicinal plant in several regions in Southeast Asia. However, this plant is still not widely known by people in various parts of the world, the number of studies that examine this plant is still relatively small, and ethnobotanical discussions about this plant are difficult to find. This study aims to provide a review of the current ethnobotanical status of Michelia alba in Java, Indonesia, which includes its biological profile, role in Javanese customs, related myths, and scientific review in terms of its pharmacological activity. The results of the ethnobotanical study revealed that this plant is fairly unique because it is often associated with magical things and is very closely related to various cultural practices of the Javanese indigenous people (kejawen). Scientifically, the results of research prove that the M. alba plant does contain various chemical constituents that have many benefits. The pharmacological activities of M. alba reported include anti-cancer, antistress, anti-fungal, antioxidant, skin protection, and effective in killing Trypanosoma parasites.